Historical and Pedagogical Information Value and Resource Potential of Creative Heritage of the Ukrainian Writers in the Research of Children’s Education Problems of the Second Half of the ХІХ c. - Haiduchenko, Yurii (Pedagogical Discourse, 2013)
In article the author clarified the informative possibilities of the Ukrainian realistic fiction of the second half of the ХІХ c. as a historical and pedagogical resource by the example of the works of Marko Vovchok, A.Svydnytskyi, I.Nechui-Levytskyi, A.Konyskyi, B.Grinchenko, N.Nomis, I. Frankо, and also the variant of a resource technique for analyzing creative heritage has been offered. The author establishes the informative resources of the Ukrainian writers about their current reality and reveals their estimation of the educational reforms consequences of second half of ХІХ c. and shows the features of children’s education of the same period. The article highlights the problems of children education of the investigated period and characterizes specificity of realistic creative heritage as a resource of historical and pedagogical knowledge.